Evaluation of the Biological Activity of some Plant Extracts Against Gram-Positive and Gram-negative Bacteria - Hbaiel, Mohammad Kareem; Kassab, Mohammed Ali; Hashim, Abdullah Hijaz (Nabatia, 2025)
The inhibitory activity of two types of plant extracts, namely the alcoholic and aqueous extracts of Capparis and Artemisia, on the growth of two types of biologically important bacteria included Bacillus cereus, a Gram-positive bacterium, and Pseudomonas aeruginosa, a Gram-negative bacterium, one of the most important opportunistic pathogens.The plant extracts were prepared at different concentrations (10, 20, and 30 mg/ml), and their effect was tested using the diffusion method in the Mueller-Hinton medium. The results showed that the alcoholic extracts were more effective in inhibiting the growth of both bacteria types than the aqueous extracts. The study demonstrated that plant extracts containing active chemical compounds, particularly alcoholic ones, could be used as effective natural antibiotics in healthcare. To pave the way for further comprehensive studies to identify these compounds, their effects, and their potential benefits. These results may contribute to the development of natural therapeutic alternatives to combat bacterial infections or be used to indicate the effectiveness of active chemical compounds present in plants by inhibiting B. cereus.